Comparison of gonial angle in lateral cephalogram and panoramic radiograph among adult patients with Class I and II skeletal pattern - Bhattarai, Anisha; Kumar Shrestha, Basanta; Prasad Sah, Madhurendra; Shrivastava, Rockey (Journal of Chitwan Medical College, 2025)
Introduction: The gonial angle is an important parameter in orthodontics for diagnosis and treatment planning. Lateral cephalograms and panoramic radiographs are commonly used for determination. The purpose of this study was to compare the gonial angle on right and left sides of panoramic imaging and lateral cephalogram. Method: This descriptive cross-sectional study was conducted at Chitwan Medical College, Nepal, from Nov 2021 to May 2023 after ethical clearance. Patients visiting for orthodontic treatment who required a lateral cephalogram and an orthopantomogram were included. Patients were categorised into Class I and II skeletal patterns based on ANB (A-Point-Nasion-B-Point) angle. Gonial angle on right and left sides of panoramic imaging was compared with lateral cephalogram. Data was checked for normality, measures of central tendency (mean, median). Gonial angle was compared (t-test for normally distributed data) between two radiograph findings and between genders, and SPSS 20 was used for analysis, with a p≤0.05 considered significant. Result: The mean gonial angle in lateral cephalogram, right and left orthopantomogram was 124.19o±6.85o, 123.43o±7.3o and 123.48o±7.3o respectively. There was a statistically significant difference in the gonial angle in cephalogram and left gonial angle in orthopantomogram among Class II skeletal patterns. On gender-based comparison, there was a statistically significant difference in all parameters. Conclusion: Orthopantomogram can be used as an alternative for gonial angle measurement in Class I skeletal patterns and only right-sided orthopantomogram among Class II skeletal patterns. The gender-based comparison showed that the gonial angle is larger in females than in males in both radiographs.